2011
DOI: 10.2304/gsch.2011.1.3.243
|View full text |Cite
|
Sign up to set email alerts
|

Global Perspectives on Children's Independent Mobility: A Socio-Cultural Comparison and Theoretical Discussion of Children's Lives in Four Countries in Asia and Africa

Abstract: The article provides a comparative analysis of children's independent mobility in four countries -South Africa, Tanzania, Japan and Australia. The authors discuss key findings across the four study sites and illustrate the contextually bound nuances connected to the data at the community level. The data illustrate that while Japanese children have the most independence generally, Japanese children who live in a small town outside of a main city centre have significantly lower mobility than their city counterpa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(34 citation statements)
references
References 26 publications
0
29
0
5
Order By: Relevance
“…Children’s independent mobility is defined as the opportunity for children to move freely in their environment without an accompanying adult, and is considered as an independent correlate of physical activity among children [19]. Independent mobility is measured in relation to spatial range or roaming range, and this measure can be determined by parents or caregivers in terms of the frontiers they set, or it can be the outcome of negotiations between children, parents or caregivers and even the community [10]. Autonomous exploration of the urban environment could provide children with opportunities for cognitive, social and physical development [33].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Children’s independent mobility is defined as the opportunity for children to move freely in their environment without an accompanying adult, and is considered as an independent correlate of physical activity among children [19]. Independent mobility is measured in relation to spatial range or roaming range, and this measure can be determined by parents or caregivers in terms of the frontiers they set, or it can be the outcome of negotiations between children, parents or caregivers and even the community [10]. Autonomous exploration of the urban environment could provide children with opportunities for cognitive, social and physical development [33].…”
Section: Discussionmentioning
confidence: 99%
“…However, the role played by parents (parental modeling) and local neighborhood environments has been subject of an increasing body of research because such information would be useful to intervention development [8,9]. Although there is limited knowledge about factors related to independent mobility in children, research considered that lost of freedom to explore and achieve mastery over physical and social environment could limit children’s opportunities to develop healthy lifestyles, social networks and environmental competence and resilience [10,11]. While studies showed that children’s levels of independent mobility might influence their physical, social, cognitive and emotional development [12] and is significantly associated with physical activity [13] it has been suggested that compared with previous generations, children today are more restricted in their independent mobility [14] In particular, parents’ perception of harm from strangers and road safety are identified as major causes of parental anxiety [15], and such concerns may cause parents to restrict their children’s outdoor play and autonomous active transport [8,16].…”
Section: Introductionmentioning
confidence: 99%
“…The independent and active mobility of children is an outcome of a very complex set of developmental (Ahmadi, 2007;Burgmanis et al, 2014;Rissotto and Tonucci, 2002), familial (Barron, 2014;Jensen et al, 2014), sociocultural (Depeau, 2001;Malone and Rudner, 2011;Valentine, 2004), and environmental characteristics (Alparone and Pacilli, 2012;Mitra and Buliung, 2014;Villanueva et al, 2013), as well as the policy context (Fyhri and Hjorthol, 2009;Rudner, 2012). Individual and family characteristics that are affecting CIM include children's age, maturity and gender (Johansson, 2006), family structure, socioeconomic status, ethnicity (Loebach and Gilliland, 2014;Weir et al, 2006), gender of parent, and parent employment (Valentine, 2004;Witten et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Lynch examined the spatial range of children of children in cities in places as diverse as Australia, Argentina and Mexico. More recent research has identified declines in 'children's independent mobility', the freedom of children to move around their own neighbourhood or city without adult supervision, in many nations (Malone and Rudner 2011). Hart explains that it was not until the 1990 publication by Hillman, Adams and Whitelegg "on the loss of children' mobility that this became one of those classic markers of how children's lives have changed" (Smith and Greene 2014, 111).…”
Section: Introductionmentioning
confidence: 99%